(q-6)*4=9

Simple and best practice solution for (q-6)*4=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (q-6)*4=9 equation:


Simplifying
(q + -6) * 4 = 9

Reorder the terms:
(-6 + q) * 4 = 9

Reorder the terms for easier multiplication:
4(-6 + q) = 9
(-6 * 4 + q * 4) = 9
(-24 + 4q) = 9

Solving
-24 + 4q = 9

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 4q = 9 + 24

Combine like terms: -24 + 24 = 0
0 + 4q = 9 + 24
4q = 9 + 24

Combine like terms: 9 + 24 = 33
4q = 33

Divide each side by '4'.
q = 8.25

Simplifying
q = 8.25

See similar equations:

| 6(3s+8)=156 | | 5(a-3)=65 | | 8x^2-2xy*-3y^2=0 | | 3+91x=39x+11 | | 2x^2=3x+12 | | 3a^2+a-10=0 | | 24-6x=12-8x | | (A-3)(3a-1)= | | -3.6r-4.5r=-6.48 | | 5.5+2.2n-4.789n=-3.3026 | | -3.5x+3.3x=0.86 | | 2(3x-4)+3(2x+2)=142 | | (x+5)(y-3)=0 | | 4x+11=-43-5x | | -4.3r-2.2r=13 | | (2z+6)(z-2)= | | m+2.6+0.26=3.76 | | xy+5y-3x=15 | | 4.79n+3.9n=-13.035 | | X-0.80X=5159 | | 20x+55y=92.65 | | 5x+x-10=20-6x | | x(2)+8=24 | | 0.837x-2.1+3.6x=17.498229 | | 3x-22=2-5x | | 3log[5](x*x-17)=log[5](x+3) | | 8-w+6=9w-2 | | Y-14=3y+4 | | 18x^3-14x^2+6x= | | 55-4y=3y+6 | | 2x^2-9xy+9y^2=0 | | 55-4y=3y+4 |

Equations solver categories